Optimizing critical parameters for the directly measurement of particle flow with PF-SIBS - Shunchun Yao (Nature Portfolio, 2018)
Abstract A novel measurement technology named as particle flow-spark induced breakdown spectroscopy (PF-SIBS) was reported for real-time measurement of solid materials. Critical measurement parameters of PF-SIBS were optimized and a set of fly ashes with different carbon content were measured for evaluation of measurement performance. Four electrode materials, tungsten, copper, molybdenum and platinum, were compared in the aspects of signal stability, line interference and electrode durability. Less line interference and better signal stability were obtained with W and Cu electrode, while W electrode has better durability. Quartz sand with diameters from 48 μm to 180 μm were tested to investigate the influence of particle size. As the particle diameter increased, the intensity of Si 288.16 nm line decreased while that of ambient air constituents increased. To reduce the particle effect, the sum intensity from sample and ambient air were introduced to correct. The RSD of line intensity between the five diameters were reduced from 67.30% to 16.59% with Cu electrodes and from 63.21% to 13.64% with W electrodes. With the optimal measurement parameters and correction, fly ash samples with different carbon content were tested and the correlation coefficients R2 of multivariate calibration achieved 0.987.